Study of using the fucoidan-containing solid media plates for screening and identifying fucoidanase from marine microorganisms - Thuan, Nguyen Thi; Thuy Hang, Cao Thi; Nhu Khanh, Huynh Hoang; Bang, Truong Hai; Thinh, Pham Duc; Thanh Van, Tran Thi; Ly, Bui Minh (Academia Journal of Biology, 2016)
Screening of microorganisms that are capable to produce  fucoidan degrading enzymes was carried out by investigating their abilities to grow on fucoidan-containing solid media plates. The activities were identified by the occurrence of a transparent areas after staining the plates with hexadecyltrimethylammonium bromide (cetavlon) 1% (w/v), which can form complexes with fucoidan. Among 44 isolated marine microorganisms strains from sea cucumber, molluscs and sea urchin, two strains produced enzyme that enable to degrade fucoidan from both seaweeds Sargassum mcclurei and S. polycystum, four strains produced enzyme degrading fucoidan only from S. mcclurei or S. polycystum. All these strains produced intracellular fucoidan-degrading enzymes.